Highly selective capture of minicircle DNA biopharmaceuticals by a novel zinc-histidine peptide conjugate - Gaspar, Vítor Manuel Abreu (2018)
Submitted by Ilídio Correia (icorreia@ubi.pt) on 2018-03-21T17:23:18Z No. of bitstreams: 1 2017 Gaspar SPT.pdf: 1582020 bytes, checksum: 296ac20e9975ebb222d7d31ce471ab07 (MD5)